Model Pasang Surut Global TPXO 7.1 sebagai Data Pendukung Penarikan Batas Wilayah Laut - Basith, Abdul (2013)
Tidal observation is supportive data for maritime boundary delimition. Using which low water levels can be determined. Basepoints from which maritime boundaries such as territorial sea is measured are required to refer low water line. In regard to this requirement, a dense of tidal stations is required. However, the number of tidal stations is relatively smaller compared to length of Indonesia coastline. As an alternatif solution, a global tidal mode, TPXO 7.1, is examined in providing tidal data by means of tidal prediction. Tidal elevations are extracted from the tidal model for six locations of tide gauge stations namely, Pangadaran, Cilacap, Prigi, Sadeng, Semarang and Jakarta. These tidal elevations are compared to those published by IOC. As the results, comparison between elevations of two different data sources show aggreements indicated by consistency of elevations of both data and the corresponding RMSE by 19 cm, 24,9 cm, 14,8 cm, 8,7 cm, 11,8 cm and 8,8 cm respectively. The results show that tidal elevations provided by TPXO 7.1 global tidal model are recommended to be used as an alternative way to provide tidal data anywhere in Indonesia waters especially at places where conventional tidal stations are unavailable as supporting data for maritime boundaries delimitation.